RESEARCH REGARDING THE PERCEPTIONS AND ATTITUDES OF MANAGERS IN POST CRISIS ROMANIA, TOWARDS MARKETING - M. O. Naghiu (Agricultura, 2014)
The present paper focuses on evaluating the impact and implications of the economic crisis on the behavior of managers in Romania towards marketing. For this a field research was applied. The research method was the survey, and the instrument used was the questionnaire. The questionnaire development was centered on the research objectives and hypotheses. The pretest phase was conducted on a sample of 15 respondents. After this stage, the final structure of the questionnaire was obtained. The survey was done on a sample of 100 subjects, managers in Romania.